Pelatihan Dasar Microsoft Office Terhadap Santriwan Santriwati Yayasan Ar-Rahman Krukut - Ade Baihaqi; Bayu Aji Laksono; Lot Martua Batu Bara Batu Bara; Mohamad Abdul Azis; Risvigo Mirfiandi; Besus Maula Sulthon Sulthon (JPM: Jurnal Pengabdian Masyarakat, 2021)
Information and Communication Technology (ICT) is currently very much needed by students and teaching staff at the Ar-Rahman Foundation. Especially for female students, training in the use of information and communication technology devices is needed so that later students can be used properly. The students and teaching staff cannot use Microsoft Excel and PowerPoint because they are not taught in schools, and the cost of computer courses is high among students in the Krukut area. One of them is to train the ability to use a word processing application, namely Microsoft Word. Community service activities are emphasized in the form of training on the application of Microsoft Office for students and teaching staff of the Ar-Rahman Krukut Foundation. It is hoped that with this training, students and teaching staff can better know the techniques of using Microsoft Office by utilizing Microsoft Word, Microsoft Excel, Microsoft PowerPoint. The results of the dedication carried out provide experience and skills for students and teaching staff in using Microsoft Office. Thus, the implementation of community service activities at the Ar-Rahman Foundation Using Microsoft Word provides significant benefits for improving the skills of students and teaching staff in utilizing information technology and computers, they are very enthusiastic to take part in the next activity. They already understand and can operate Microsoft Office.